2015
DOI: 10.1063/1.4930265
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear heavy ion-acoustic waves in a strongly coupled plasma

Abstract: A theoretical study on the propagation of linear and nonlinear heavy ion-acoustic (HIA) waves in an unmagnetized, collisionless, strongly coupled plasma system has been carried out. The plasma system is assumed to contain adiabatic positively charged inertial heavy ion fluids, nonextensive distributed electrons, and Maxwellian light ions. The normal mode analysis is used to study the linear behaviour. On the other hand, the well-known reductive perturbation technique is used to derive the nonlinear dynamical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…As streaming provides extra energy to the system, the soliton receives more energy and moves to a higher supersonic regime. Such consequences are demonstrated exactly for nonlinear heavy IA waves in a strongly coupled plasma in planar [39] and non-planar [40] geometry. This demonstrates that, in the presence of fixed values of non-extensivity and ion streaming, the Mach number is decreasing with trapping probability.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…As streaming provides extra energy to the system, the soliton receives more energy and moves to a higher supersonic regime. Such consequences are demonstrated exactly for nonlinear heavy IA waves in a strongly coupled plasma in planar [39] and non-planar [40] geometry. This demonstrates that, in the presence of fixed values of non-extensivity and ion streaming, the Mach number is decreasing with trapping probability.…”
Section: Resultsmentioning
confidence: 77%
“…The enhancing values of q decrease the superthermality factor and therefore minify the electron energy, and in order to conserve the energy, the energy of ions increases, accordingly increasing the DIA soliton energy. Such consequences are demonstrated exactly for nonlinear heavy IA waves in a strongly coupled plasma in planar [39] and non-planar [40] geometry.…”
Section: Resultsmentioning
confidence: 77%
“…It is important to not that the dissipation term only depends on the electron kinematic viscosity η. The shock profile is nothing but sudden increase or decrease of the permanent profile of the waves [75][76][77][78]. It is observed that EA waves are significantly modified when cold electron being non-relativistic degenerate (α = 5 3 ) and hot electron being ultra-relativistic degenerate (γ = 4 3 ) than both cold and hot electron being non-relativistic degenerate (α = γ = 5…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…[ 3 ] Experimental studies of ion‐acoustic waves (IAWs) in negative‐ion plasmas were reported by Song et al [ 4 ] and Wong et al [ 5 ] Linear and nonlinear properties of IAWs have been widely investigated theoretically by authors. [ 6–13 ] In the presence of dust impurities in the ordinary plasma, IAWs lead to the so‐called dust‐ion acoustic waves (DIAWs). [ 14 ] The propagation of DIAWs in an inhomogeneous dusty plasma was shown.…”
Section: Introductionmentioning
confidence: 99%